Bride wars [videorecording (DVD)] - Hudson, Kate, 1979-; Winick, Gary, 1961-2011; Hathaway, Anne, 1982-; Greenberg, Bryan (20th Century Fox Home Entertainment, 2009)
Lifelong best friends Liv and Emma have shared a dream since childhood. Each yearns for the perfect June wedding at the famed Plaza Hotel in New York City. Both find themselves engaged at the same time and go to a wedding coordinator to set up the perfect wedding. A clerical error puts them both down for nuptials on the same day at the same time. One of them will have to switch the date. More than the bouquet goes flying when these desperate brides-to-be fight it out for matrimonial supremacy.